2015
DOI: 10.1097/md.0000000000000643
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Tumor Necrosis Factor-α, Heat Shock Protein 70, Malondialdehyde, and Superoxide Dismutase in Patients With Different Severities of Alcoholic Fatty Liver Disease

Abstract: The relationships among inflammation, oxidative balance, and the severity of alcoholic fatty liver disease (AFLD) remain unknown. The aim of this study is to explore the relationships among tumor necrosis factor alpha (TNF-α), heat shock protein 70 (HSP70), malondialdehyde (MDA), superoxide dismutase (SOD), and the severity of AFLD.From January 2012 to December 2013, 162 participants were enrolled in this study and divided into 4 groups: 44 cases of mild AFLD (group A), 55 cases of moderate-to-severe AFLD (gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
(40 reference statements)
1
7
0
Order By: Relevance
“…OS and inflammation have been confirmed in patients with ALD, in several studies. Qu et al [ 134 ], observed that heat shock protein 70 (HSP70), an intracellular polypeptide involved in immune responses, contributing to vascular damage and TNF-α release, was increased in alcoholic fatty liver disease. Grasselli et al (2014) [ 135 ] also identified a redox imbalance in ALD subjects: increase of lipid peroxidation and stimulation of the activities of the antioxidant enzymes CAT and SOD [ 135 ].…”
Section: Discussionmentioning
confidence: 99%
“…OS and inflammation have been confirmed in patients with ALD, in several studies. Qu et al [ 134 ], observed that heat shock protein 70 (HSP70), an intracellular polypeptide involved in immune responses, contributing to vascular damage and TNF-α release, was increased in alcoholic fatty liver disease. Grasselli et al (2014) [ 135 ] also identified a redox imbalance in ALD subjects: increase of lipid peroxidation and stimulation of the activities of the antioxidant enzymes CAT and SOD [ 135 ].…”
Section: Discussionmentioning
confidence: 99%
“…The protocol was approved by the clinical research ethics committee of Taishan Hospital in Shandong Province. The exclusion criteria for the subjects have been described in a previous publication 14 .…”
Section: Methodsmentioning
confidence: 99%
“… 11 Our previous study showed that CIMT correlated with age and metabolic factors in subjects with alcoholic fatty liver disease. 12 Additionally, previous studies have shown that the CIMT quartile is significantly higher in subjects with a higher BMI. 13 , 14 The present study found that among patients who ingested alcohol, those with increased CIMT were older than were those with a normal CIMT.…”
Section: Discussionmentioning
confidence: 96%